Detection of planktonic coenzyme factor 430 in a freshwater lake: small-scale analysis for probing archaeal methanogenesis - Atsushi Urai (SpringerOpen, 2021)
Abstract We present the first data describing molecular evidence of planktonic coenzyme factor 430 (hereafter referred to as F430), a key signature of methanogenic archaea, obtained from a water column sample in a freshwater lake in Japan. We report concentrations of native F430 ranging from 6.8–35 × 102 femto mol g-wet−1 and 8.5–86 × 102 femto mol g-wet−1 in the water column and core-top sediment, respectively. Among these profiles, the epimer F430 of the deactivated chemical formula was very low overall in both planktonic and benthic environments. Small subunit (SSU) rRNA gene sequencing revealed that the planktonic microbial community was clearly different from that of the benthic sediment. Planktonic cyanobacteria (e.g., Microcystis) were predominant in the water column, whereas a wide variety of bacteria and archaea, including methanogens (e.g., Methanobacterium, Methanoregula, Methanothrix, Methanosarcina, and Methanocella), were observed in the core-top sediment. These results suggest that the planktonic cyanobacterial community may be rapidly degraded at the water–sediment interface driven by activated benthic microbial heterotrophic processes. Graphic abstract